THE GENESIS OF THE STABLE ISOTOPE (O, H) RECORD IN ARC MAGMAS: THE KAMTCHATKA'S CASE - Pineau F.; Grassineau N.; Javoy M.; Semet M.P.; Okrugin V.M. (My University, 1999)
We have determined δ18O in 120 chemically well-documented samples of lavas characteristic of the major areas and types of volcanism, most of which Quaternary in age, from the subduction zone volcanism in the Kamchatka peninsula, far-eastern Russia. Hydrogen isotopic data have also been obtained on about half of the samples. This volcanism has been highly active from the Cretaceous to the present and results from high convergence rates between the North Pacific plate and the Northeastern part of the Eurasian plate. The peninsula is the northernmost extension of the Japan–Hokkaido–Kurile Island Arc that runs continuously over about 2000 km. Hundreds of Quaternary arc-related volcanic edifices occupy its two main areas: the Eastern Volcanic Front (EVF), and the Central Kamchatka Depression (CKD). In Kamchatka, the contributions of sediments and continental crust are low, which makes easier the specific evaluation of the mantle wedge and the descending slab contributions. δ18O range from 5.3 to 8.5‰, δD from −70 to −212‰ and water contents from 0.01 to 0.9% in basic lavas. This high scatter is pristine and inherited from the mantle source of the magmas. Comparable ranges and scatter in evolved lavas (andesites to rhyolites) are mainly due also to parent magma variability. Combined δ18O, δD values and H2O contents are explained in terms of a mixing, differentiation and degassing model. All the lavas result from mixtures of normal mantle magmas with a slab-derived, water-rich fluid/magma which is an essentially equimolecular mixture of water and plagioclase-like silicates, together with Mg and Fe concentrations around 1 and 3%, respectively. The average initial water concentration in the resulting lavas is 5.5%. If that characteristic concentration is a general feature in subduction zones, this would correspond to an upward volcanic and plutonic water flux of around 1015 g/year. That `leakage' flux equilibrates the flux subducted through sediments and hydrated oceanic crust so that the remaining flux subducted into the mantle is of the order of the ridge flux. The water flux could be a significant part of the water involved at mid crustal levels in anatexis phenomena and explain the convergence of granites' δ18O's towards the 8.5–10‰ range.
Keywords: Quaternary; Cretaceous; Кайнозой::Четвертичная; Mesozoic::Cretaceous; Cenozoic::Quaternary; Мезозой::Меловая